ISIS: Inside the army of terror. By Michael Weiss and Hassan Hassan. Regan Arts. New York, 2015. Pp. 270. ISBN: 978-1-941393-57-4 - Abdel Salam, El Fatih Abdullahi (Bangladesh Institute of Islamic Thought, 2017)
With brutal force and horrific beheadings of hostages, the Islamic State of Iraq and Syria (ISIS) has shocked the world. They have conquered massive territories in both countries – equal to the size of the United Kingdom – and promise to create a new Muslim caliphate under the strict dictates of Sharia law.